Leadership effectiveness in improving employee performance - Dzikriana, Syakila; Samtiarico, Revany; Nahriyah, Lailatul; Haryadi, Didit; Wahyudi, Wahyudi (Trigin Publisher, 2024)
Effective management, thinking about the importance of human resources. Employee performance is an important factor influencing success. In an organization, this is one of the most important functions of a company. This study aims to determine the variables that affect employee job satisfaction and develop a theoretical basis and research model. This study used an associative descriptive quantitative method with a population of 35 respondents drawn into a sample using non-probability sampling, using saturated sampling / total sampling method. Data analysis techniques using linear regression with the help of SPSS software version 26. The results of this study show that the first hypothesis states that employee performance is influenced by leadership style; the more effective the leader makes decisions, the more employee performance increases. The second hypothesis states that communication shows no significant effect on employee performance. The third hypothesis is that employee performance is influenced by employee leadership and communication styles that can simultaneously improve employee performance. This research is expected to provide theoretical contributions to the literature in this context, certainly in the context of human resource management